The greatest shows on earth : a history of the circus - Simon, Linda, 1946- (Reaktion Books, 2014)
Step right up! and buy a ticket to the Greatest Show on Earth - the Big Top, containing death-defying stunts, dancing bears, roaring tigers, and trumpeting elephants. The circus has always been home to the dazzling and the exotic, the improbable and the impossible--a place of myth and romance, of reinvention, rebirth, second acts, and new identities. Asking why we long to soar on flying trapezes, ride bareback on spangled horses, and parade through the streets in costumes of glitter and gold, this captivating book illuminates the history of the circus and the claim it has on the imaginations of artists, writers, and people around the world --